Polygamy in Northern Malawi : A Christian Reassessment - Mlenga, Moses (Book collections on Project MUSE., 2016)
The early missionaries brought Christianity from the monogamous West to the polygamous societies of Africa. Were the missionaries right in demanding that converts dismiss all but one wife? Was this the demand of the Christian faith or of Western civilization? And were the converts right to dismiss their wives though they had married them according to the laws of the land? And who asked the children if they wanted their mothers to be dismissed and may or may not be married to another man? The book argues that while polygamy is an African reality, it is below Christian moral standards. However is stopping converted polygamous men and women from baptism best practice if we believe that sin can be forgiven for the one who repents? Can the shedding of responsibility for wives and children be made a precondition for such forgiveness?